Statistical characteristics of particle injections throughout the equatorial magnetotail. Issue 4 (2nd April 2014) - Gabrielse, C.; Angelopoulos, V.; Runov, A.; Turner, D. L.
Abstract Energetic particle injections are critical for supplying particles and energy to the inner magnetosphere. Recent case studies have demonstrated a good correlation between injections and transient, narrow, fast flow channels as well as earthward reconnection (dipolarization) fronts in the magnetotail, but statistical observations beyond geosynchronous orbit (GEO) to verify the findings were lacking. By surveying trans‐geosynchronous injections using Time History of Events and Macroscale Interactions during Substorms (THEMIS), we show that their likely origin is the earthward traveling, dipolarizing flux bundles following near‐Earth reconnection. The good correlation between injections and fast flows, reconnection fronts and impulsive, dawn‐dusk electric field increases is not limited to within 12 RE but extends out to 30 RE. Like near‐Earth reconnection, both ion and electron injections are most probable in the premidnight sector. Similar to bursty bulk flows (BBFs), injection‐time flow speeds are faster farther from Earth. With faster flows, injection intensity generally increases and extends to higher energy channels. With increased geomagnetic activity, injection occurrence rate increases (akin to that of BBFs) and spectral hardening occurs (κ decreases). The occurrence rate increase within the inner magnetosphere suggests that injections populate the radiation belts more effectively under enhanced activity. Our results are inconsistent with the classical concept of an azimuthally wide injection boundary moving earthward from ~9 to 12 RE to GEO under an enhanced cross‐tail electric field. Rather, particle injection and transport occur along a large range of radial distances due to effects from earthward penetrating, azimuthally localized, transient, strong electric fields of recently reconnected, dipolarizing flux bundles.